Phase I dose-escalation and pharmacokinetic study of a novel folate analogue AG2034 - Bissett, D (Nature Publishing Group, 2001)
The novel folate analogue AG2034, which was designed as an inhibitor of GARFT (glycinamide ribonucleotide formyltransferase), was evaluated in this phase I study under the auspices of The Cancer Research Campaign, UK. AG2034 blocks de novo purine synthesis through inhibition of GARFT. A total of 28 patients with histologically proven intractable cancers were enrolled. AG2034 was administered as a short intravenous infusion once every 3 weeks. 8 dose levels ranging from 1–11 mg/m(2) were evaluated with patients receiving up to 6 cycles. Dose-limiting toxicities in the form of mucositis, diarrhoea and vomiting were observed at doses of 6 mg/m(2) and above. Significant levels of thrombocytopenia, neutropenia and anaemia were also recorded. Other sporadic toxicities included fatigue and myalgia. The MTD with this schedule of AG2034 was 5 mg/m(2). Most side effects occurred more frequently with cumulative dosing. In keeping with this, pharmacokinetic analysis revealed evidence of drug accumulation. The AG2034 AUC(0–24) increased by a median of 184% (range 20–389%) from cycle 1 to 3 in all 10 patients examined. No objective antitumour responses were observed in the study. © 2001 Cancer Research Campaign http://www.bjcancer.com